Boosting targeted genome editing using the hei-tag - Thumberger, Thomas; Tavhelidse-Suck, Tinatini; Gutiérrez Triana, José Arturo; Cornean, Alex; Medert, Rebekka; Welz, Bettina; Freichel, Marc; Wittbrodt, Joachim (eLife, 2022)
Precise, targeted genome editing by CRISPR/Cas9 is key for basic research and translational approaches in model and non-model systems. While active in all species tested so far, editing efficiencies still leave room for improvement. The bacterial Cas9 needs to be efficiently shuttled into the nucleus as attempted by fusion with nuclear localization signals (NLSs). Additional peptide tags such as FLAG- or myc-tags are usually added for immediate detection or straightforward purification. Immediate activity is usually granted by administration of preassembled protein/RNA complexes. We present the ‘hei-tag (high efficiency-tag)’ which boosts the activity of CRISPR/Cas genome editing tools already when supplied as mRNA. The addition of the hei-tag, a myc-tag coupled to an optimized NLS via a flexible linker, to Cas9 or a C-to-T (cytosine-to-thymine) base editor dramatically enhances the respective targeting efficiency. This results in an increase in bi-allelic editing, yet reduction of allele variance, indicating an immediate activity even at early developmental stages. The hei-tag boost is active in model systems ranging from fish to mammals, including tissue culture applications. The simple addition of the hei-tag allows to instantly upgrade existing and potentially highly adapted systems as well as to establish novel highly efficient tools immediately applicable at the mRNA level.
Gesehen am 30.01.2023